Casimir energy corrections by light-cone fluctuations - Arias, E.; Dueñas, J. G.; Svaiter, N. F.; Bessa, C. H.G.; Menezes, G. [UNESP] (World Scientific Publishing, 2014)
We study the effects of light-cone fluctuations on the renormalized zero-point energy associated with a free massless scalar field in the presence of boundaries. In order to simulate light-cone fluctuations, we introduce a space-time dependent random coefficient in the Klein-Gordon operator. We assume that the field is defined in a domain with one confined direction. For simplicity, we choose the symmetric case of two parallel plates separated by a distance a. The correction to the renormalized vacuum energy density between the plates goes as 1/a8 instead of the usual 1/a4 dependence for the free case. In turn, we also show that light-cone fluctuations break down the vacuum pressure homogeneity between the plates. © 2014 World Scientific Publishing Company.
Keywords: Casimir energy; Quantum fields in curved space-time; Wave propagation in random media